2022
DOI: 10.1017/s1431927622000496
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion Beam Preparation of Low Melting Point Metals: Lessons Learned From Indium

Abstract: Indium (In) and other low melting point metals are used as interconnects in a variety of hybridized circuits and a full understanding of the metallurgy of these interconnects is important to the reliability and performance of the devices. This paper shows that room temperature focused ion beam (FIB) preparation of cross-sections, using Ga+ or Xe+ can result in artifacts that obscure the true In microbump structure. The use of modified milling strategies to minimize the increased local sample temperature are sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…interest, but they are destructive and require direct line-of-sight access to the failure region. 8,9 Methods such as confocal scanning acoustic microscopy offer a picture of debonded regions, but are resolution limited. 10 Recent work has shown that nondestructive evaluation of bond quality can be achieved with high spatial resolution using Brillouin-Mandelstam light scattering spectroscopy to probe energies in acoustic phonons and velocities of Rayleigh acoustic waves at interfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…interest, but they are destructive and require direct line-of-sight access to the failure region. 8,9 Methods such as confocal scanning acoustic microscopy offer a picture of debonded regions, but are resolution limited. 10 Recent work has shown that nondestructive evaluation of bond quality can be achieved with high spatial resolution using Brillouin-Mandelstam light scattering spectroscopy to probe energies in acoustic phonons and velocities of Rayleigh acoustic waves at interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…To understand how bond quality is affected by fabrication processes as well as assembly operations, more advanced characterization and failure analysis methods are needed. Current techniques such as electron microscopy can provide extensive information about local bond quality at a region of interest, but they are destructive and require direct line-of-sight access to the failure region. , Methods such as confocal scanning acoustic microscopy offer a picture of debonded regions, but are resolution limited . Recent work has shown that nondestructive evaluation of bond quality can be achieved with high spatial resolution using Brillouin-Mandelstam light scattering spectroscopy to probe energies in acoustic phonons and velocities of Rayleigh acoustic waves at interfaces …”
Section: Introductionmentioning
confidence: 99%